PEMANFAATAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR UNTUK MENINGKATKAN HASIL BELAJAR FIQIH MATERI HAJI DAN UMRAH DI KELAS VIII MTs AL-JAMIYATUL WASHLIYAH MEDAN - Rizki Habibi (Fakultas Agama Islam, 2021)
The purpose of this study was to determine how the use of the school environment as a source of Fiqh learning in improving Fiqh learning outcomes for Hajj and Umrah materials, what factors were supporting and inhibiting the use of the school environment as a source of Fiqh learning in improving students' Fiqh learning outcomes. This type of research is descriptive quantitative. The population of this study were students of class VIII MTs Al-Jamiyatul Washliyah Jalan Ismailiyah Number 82 Medan, totaling 108 students. The sample was selected using a purposive sample technique (purposed sample), namely 40 students in class VIII.1. Data collection techniques were carried out through non-test, namely questionnaires and interviews. The results showed that the use of the school environment as a source of Fiqh learning included the use of mosques, libraries, internet, computer laboratories, and tools. All of these learning resources are used optimally by teachers and students with careful planning and strong motivation to use them, so the Fiqh learning resources on the MTs Al-Jamiyatul Washliyah Medan page contribute to improving student learning outcomes, especially on Hajj and Umrah materials. supporters of the use of the school yard as a source of fiqh learning include: motivation from teachers, student attention, parental attention, and the availability of supportive learning resources, while inhibiting factors include: lack of student motivation, limited media or available tools, and lack of funds. student learning increases after teachers and students utilize the school yard as a learning resource to the fullest. This is evidenced by the increasing results of students' daily tests on the material for Hajj and Umrah before utilizing learning resources and after utilizing learning resources.